Promising Farmers’ choicest mango – Vanlaxmi - Patel, C. R.; Shah, N. I.; Misra, A. K. (Indian Horticulture, 2019)
There is an urgent need to undertake extensive research on Vanlaxmi mango variety not only at regional level but also at national level. This variety has yield and quality characters suitable for becoming an ideal mango variety which is good for table purpose and excellent for domestic as well as export market. The variety proved its yield potential at farmers’ fields and can play important role in future mango cultivation.